Wideband Direction-of-Arrival Estimation via Covariance Fitting and Focusing - Wu, Xunmeng; Yang, Zai; Wei, Zhiqiang; Schober, Robert; Xu, Zongben (European Signal Processing Conference, 2024)
This paper studies the problem of direction-of-arrival (DOA) estimation for multiple wideband source signals using a uniform linear array. We propose a covariance fitting and focusing-based estimation method (COFFEE). Specifically, we develop a wideband covariance fitting criterion and formulate a corresponding bilevel optimization problem by introducing focusing operations on covariance matrices. We show that the upper-level problem for covariance fitting can be cast as a rank-constrained semidefinite programming (SDP) and the lower-level problem for the focusing matrices has a closed-form solution. We develop an alternating direction method of multipliers algorithm for the rank-constrained SDP. We further propose an alternating iterative algorithm to solve the overall bilevel optimization problem. Numerical results demonstrate that COFFEE outperforms existing methods.
CRIS-Team Scopus Importer:2024-11-15
Keywords: bilevel optimization; covariance fitting; focusing; Wideband DOA estimation